Product technology road mapping back contact module technology - Diesta, Noel Gonzales (University of the Philippines Diliman, 2012)
PV today provides 0.1 percent of total global electricity consumption and it is projected to grow by 5 percent in 2030 of global electricity consumption rising to 11 percent in 2050 according to IEA (2010). Because of this growing demand for renewable energy, there are many solar companies that came along all over the world from China, Europe, America, Japan, India and Austria. And China is one of those countries with many companies involved in the manufacturing of solar PV modules. China's domestic output of PV cells expanded from less than 100 MW in 2005 to 2 GW in 2008, experiencing a 20-fold increase in just four years (IEA, 2010). India on the other hand has around 50 assemblers of various kinds and can supply 200 MW per year. Our company, being a European company is also involved in the manufacturing of solar wafer, solar cells, solar modules, and systems. And in fact, we are present in the entire value chain from growing of silicon ingot to installing the modules in the field. Because of the rapid increase in the number of PV manufacturers offering low cost solar cells and modules (particularly coming from China) coupled with the reduction in feed in tariffs from different countries, the competition has become so tight that some of the companies have reduced the capacity of operation or worst, closed the business. It is due to the above mentioned competition that surviving companies have to go through the pain of cost reduction, improving or optimizing the current technology, and or pursuing new technology platforms to be at par or exceed the competition. Cost reduction can only go a certain distance as far as reducing the price of solar PV is concerned. On the other hand, new technology platform or novel technology will take a long time to market and will not be beneficial as an immediate solution to the cost problem. This is why improving or optimizing the current technology is the most viable solution to survive. And improving the conversion efficiency of a solar cell and solar module is one of the major ways of beating the competition. For solar companies in the area of crystalline silicon, SunPower and Sanyo have the highest efficiency mass produced solar cells and modules. No wonder that their IPs is well protected by patents. For the rest of the solar companies making the front contact technology, Metal Wrap Through (MWT) is one of the best ways of improving the efficiency of back contact solar cell and solar modules. The purpose of this paper is to present an analysis on the selection of a Metal Wrap Through (MWT) technology in order increase module efficiency thru technology roadmapping. The details of the development methodology on a firm level are also presented. And finally, the main output of this report is a technology roadmap illustrating how new technologies will fit into the existing product or series of products to attain improvements of solar PV efficiency. This roadmap will play a very important and critical role to our company. This will be the basis of spending millions of Euros for development cost, materials and equipments/machines for mass producing the improved product. Also, it serves as another form of investment for our company's overall strategic plan. This report is organized by bringing together market and product information together with the technology information to create a technology roadmap. Market, Product and Technology information were gathered thru : interviews, and discussions with equipment suppliers/manufacturers and materials suppliers : visit and consultation with PV research institutions; attending conferences and workshops, and conducting simple experiments. Actual experiment results are cited and real market information is presented. Thru visit with research institutions, interviews and discussion with materials and equipment suppliers, attending conferences and workshops, conducting experiments, subscription to technical journal and web literature search, we are able to successfully bring together market, product and technology information to create a product technology roadmap that will boost product efficiency in order to alleviate, if not to solve the dramatic decrease in price of solar PV modules and to stay competitive, i.e. thru MWT. Using roadmapping process, we are able to explain how these information can be brought together to make way for product technology development and with the use of graphical format, we are able to clearly illustrate how the series of products will be introduced or developed with respect to desired efficiency and thru time. Other solar PV companies can also use the roadmap presented in figure 5 as a guide for their product development.